PEMILIHAN TWEEDE KAMER BELANDA DAN MASALAH KEMISKINAN DI INDONESIA DALAM NARASI SURAT KABAR ADIL TAHUN 1933 - Muhammad Aslambik; Syamsul Bakri (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2023)
The present study aimed to discover how the Adil newspapers reported various problems in 1933. This research focused on political problems in the Netherlands and the impacts on the life of the nation and the people of Indonesia, which was still a Dutch colony at that time. In addition, this study also explained the Indonesian people's economic conditions during that period. This research used the theory of patron-client relationship patterns, where rulers have the authority to regulate the lives of their people, and people depend on the policies of their rulers. The findings showed that the capitalist and conservative parties had dominated the Tweede Kamer. Finally, the Indonesian people's economy was also classified as poor, which caused other crimes. Key words: Adil newspaper, Tweede Kamer of the Netherlands, poverty Keywords: Adil Newspaper, Tweede Kamer of the Netherlands, poverty